Signal - Christian Boltanski - Jussen, Bernhard 1959- Hrsg; Boltanski, Christian 1944-2021 (Von der künstlerischen Produktion der Geschichte, 2004)
Liturgies of disappearing: material references in art and religion / Thomas Lentes -- Christian Boltanski: memoria and cultural memory / Otto Gerhard Oexle -- Images stimuli: Boltanski's art after the Holocaust / Monika Steinhauser